United Kingdom : Financial Sector Assessment Program-Detailed Assessment of Observance of Insurance Core Principles Issued by the International Association of Insurance Supervisors. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
The regulatory framework for insurance supervision in the United Kingdom is sophisticated and the authorities are leaders in supervisory techniques. Observance with the Insurance Core Principles (ICPs) is very high compared to peers with 17 ICPs observed and only 6 out of 24 ICPs determined to be largely observed and 1 partly observed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Money and Monetary Policy